Thermostable heat-insulating composite materials based on hollow microspheres and solid phosphate binders: development and research - Apanasevich, Natalia S.; Sokal, Aliaksei A.; Kudlash, Alexander N.; Lapko, Konstantin N.; Siomikha, Alesia Yu.; Yerakhavets, Aliaksandra M. (Journal of the Belarusian State University. Chemistry, 2022)
Thermostable heat-insulating composite materials based on solid magnesium phosphate and calcium phosphate binders, fly-ash and glass hollow microspheres have been developed and proposed. Thermal and phase transformations have been studied as well as strength characteristics of the initial composites and products of their thermal treatment up to 1000 °C have been determined. It is shown that the prepared phosphate composites are thermally stable in the temperature range of 20 –1000 °С, have a density 0.4 – 0.6 g/cm3 , thermal conductivity 0.11– 0.19 W/(m ⋅ K) and show sufficiently high strength properties (compressive strength 1.4 –3.2 MPa).